Patients: A Systematic Literature Review Medication Companions For Tuberculosis - Rusyanti, Siti; Handayani, Hani (Jurnal Ners, 2025)
Tuberculosis (TB) is a global health problem that requires long-term treatment. Patient adherence to therapy plays a crucial role in achieving recovery and preventing drug resistance. This study used a Systematic Literature Review method to evaluate the contribution of Medication Companions (PMO) in improving TB treatment adherence and success, while also identifying factors influencing their effectiveness. The analysis showed that the presence of PMO plays a significant role in encouraging patient adherence to medication through various forms of support, such as instrumental, emotional, informative, and appreciative support. The presence of effective PMO is also correlated with high patient recovery rates. However, the effectiveness of mentoring is influenced by several obstacles, including limited formal training, social stigma, psychosocial issues, and economic constraints. In conclusion, PMO are a crucial element in TB control strategies, but achieving long-term results requires a more comprehensive approach through increasing PMO capacity, reducing social stigma, and providing comprehensive support for patients.